Water stream under the acoustic field from a small pipe - Mui, Keith Ka-Ho (2019)
Droplet generation has been a technology used in many applications such as printing, manufacturing. In this project the physics behind it is investigated at a larger scale than what is usually used in such technologies which involves droplets in microns and the use of micropores. Using a relatively simple setup, this project details an experiment conducted to investigate the effects of sound waves on a water stream and its ability to split it into droplets of varying diameters and even altering its trajectory in certain cases to create wave-like patterns in its motion like the shape of a sine wave. An observation was made that the distance before the water stream breaks into droplets tends to decrease as the voltage increases. Also, the higher the frequency, the greater the mean vertical diameter of droplets, and the smoother the oscillations of the pressure amplitudes in the duct. The voltage has its impact on the distance to break, and the pressure, where the greater the voltage is, the shorter the distance from the nozzle before the water stream breaks into droplets and the smoother oscillations of the pressure amplitude. Overall the experiment helped to understand the effects that sound waves have on a stream of water, at various frequencies, flowrates, and voltages. There were however limitations to the experiment in terms of the equipment used, mainly because many components of this experiment were not rigid enough to not be affected by the unwanted vibrations from the speaker. In the future work, it is proposed to conduct the experiment with two speakers facing each other instead of one, with the water stream at the centre of it, to observe the effects of superposition on the water stream with more than one source of sound waves incident on it.